Optimization of Maintenance and Supervision of Deck Crane Wire on Mv. Daidan Pertiwi - Marihot Simanjuntak; April Gunawan Malau; Sajim Budi Setiawan; Sulthan Pasha Ibrahim (Dinasti International Journal of Education Management And Social Science, 2022)
The smooth operation of the ship is determined by the operational conditions of the ship when carrying out loading and unloading operational activities and administrative management at the port of origin and port of destination. So when the performance of the deck crane is disturbed, it will affect the loading and unloading process. Damage to the motor or breaking of the wire rope will cause loading and unloading activities to be disrupted so that the next process will be hampered. Based on these problems, the author conducts an analysis to determine whether there are factors causing the breaking of the hoisting wire and the cause of the less than optimal performance of the supervisory officer of the guard in loading and unloading activities. The type of research used is a qualitative method. Data collection was carried out by conducting observations, verbal interviews with the ship's crew, and direct research to the object of research by carrying out marine practices on the MV ship. Daidan Pertiwi. Conclusions in this study were carried out by comparing those obtained from respondents' answers in the form of relevant theoretical and scientific data which were analyzed by qualitative descriptive analysis. Based on the acquisition of questionnaire data and data processing. The results showed that the maintenance of loading and unloading equipment and the lack of optimal performance of the supervision of the guard officers during loading and unloading together proved to be positive and significant to the delay in the loading process on the MV. Daidan Pertiwi. The author describes several solutions to overcome damage to loading and unloading equipment, namely: the company and the MV crew. Daidan Pertiwi must make efforts to implement PMS (planned maintenance system) in terms of maintenance of loading and unloading equipment on board and implement working hours in accordance with MLC 2006 (Maritime Labor Convention) as well as add guard personnel to facilitate supervision during loading and unloading activities. so that there are no obstacles and a positive influence on the delay in the loading process due to damage to the loading and unloading equipment in the MV. Daidan Pertiwi.